Steam reforming of acetic acid over Ni/Al2O3 catalyst: Correlation of calcination temperature with the interaction of nickel and alumina - Zhang, C.; Hu, X.; Zhang, Z.; Zhang, L.; Dong, Dehua; Gao, G.; Westerhof, R.; Syed-Hassan, S. (Elsevier Ltd, 2018)
This study investigated the interaction of nickel species with alumina versus calcination temperature and nickel loading. A total of 22 Ni/Al 2 O 3 catalysts, calcined at the temperature from 500 to 1000 °C at a 50 °C increment, were employed for the study. High calcination temperature led to the formation of nickel–alumina spinel via the solid phase reaction, which shifted the reduction temperature to higher ranges. The catalyst, however, still achieved good activity after full reduction of the nickel–alumina spinel. Nevertheless, the high calcination temperature led to the collapse of the small pores and the formation of the big one, resulting in the significant decrease of specific surface area. At higher nickel loadings, more nickel species weakly interacted with alumina formed as the reactive center of alumina was saturated. With the increase of nickel loading, the catalytic activities were not varied much but the catalytic stability and the resistivity towards coking enhanced. The coke produced over the catalyst at low nickel loading tended to be amorphous, while the coke produced at the high nickel loading was more fibrous. Furthermore, the coke produced at the low loading contained more small aromatic rings and more oxygen-containing functional groups. The higher nickel loading possibly promoted the catalytic cracking reactions to form more catalytic coke while the low nickel loading probably favored the polymerization reactions to form the polymeric coke. In addition, the calcination at the higher temperature could enhance the stability of the catalysts, which might be related to the enlarged pore sizes.